The dryad storm ebook - Forest, Laurie (The Black Witch Chronicles, 2025)
The New York Times bestselling series! Magical forces clash and Erthia hovers on the brink of ruin in the can't-miss finale of Laurie Forest's epic fantasy series, The Black Witch Chronicles! Who can survive the Shadow storm? Black Witch of prophecy Elloren Gardner Grey has unleashed her powers and embraced her legacy as a Dryad and guardian of the Forest. But the losses—of life, of love—have been almost too great to withstand as the Shadow continues to devour the world. With only a tattered shred of hope remaining, the Bearers of the Wand of Myth must battle their way back to each other to mount a final stand. But Elloren and her allies are not only facing Mage Vogel's advancing forces—the armies of the Eastern Realm will stop at nothing to see the Black Witch struck down. With Elloren's bonded mate prophesied to kill her, Shadow demons rising, and the ties between allies unraveling, can this fracturing world unite to face down the coming storm? Read all the books in the Black Witch Chronicles! The Black Witch The Iron Flower The Shadow Wand The Demon Tide The Dryad Storm Wandfasted (prequel ebook)* Light Mage (prequel ebook)* *Also available in print in The Rebel Mages anthology